FANCD2 and HES1 suppress inflammation‐induced PPARɣ to prevent haematopoietic stem cell exhaustion. (22nd November 2020) - Wu, Limei; Li, Xue; Lin, Qiqi; Chowdhury, Fabliha; Mazumder, Md H.; Du, Wei
Summary: The Fanconi anaemia protein FANCD2 suppresses PPARƔ to maintain haematopoietic stem cell's (HSC) function; however, the underlying mechanism is not known. Here we show that FANCD2 acts in concert with the Notch target HES1 to suppress inflammation‐induced PPARƔ in HSC maintenance. Loss of HES1 exacerbates FANCD2 ‐KO HSC defects. However, deletion of HES1 does not cause more severe inflammation‐mediated HSC defects in FANCD2 ‐KO mice, indicating that both FANCD2 and HES1 are required for limiting detrimental effects of inflammation on HSCs. Further analysis shows that both FANCD2 and HES1 are required for transcriptional repression of inflammation‐activated PPARg promoter. Inflammation orchestrates an overlapping transcriptional programme in HSPCs deficient for FANCD2 and HES1, featuring upregulation of genes in fatty acid oxidation (FAO) and oxidative phosphorylation. Loss of FANCD2 or HES1 augments both basal and inflammation‐primed FAO. Targeted inhibition of PPARƔ or the mitochondrial carnitine palmitoyltransferase‐1 (CPT1) reduces FAO and ameliorates HSC defects in inflammation‐primed HSPCs deleted for FANCD2 or HES1 or both. Finally, depletion of PPARg or CPT1 restores quiescence in these mutant HSCs under inflammatory stress. Our results suggest that this novel FANCD2/HES1/PPARƔ axis may constitute a key component of immunometabolic regulation, connecting inflammation, cellular metabolism and HSC function.